Refugees, asylum-seekers and undocumented migrants and the experience of parenthood: a synthesis of the qualitative literature - Merry, Lisa; Pelaez, Sandra; Edwards, Nancy C (Université d'Ottawa | University of Ottawa, 2017)
Abstract Objective To synthesize the recent qualitative literature and identify the integrative themes describing the parenthood experiences of refugees, asylum-seekers and undocumented migrants. Methods We searched seven online databases for the period January 2006 to February 2017. We included English and French published peer-reviewed articles and graduate-level dissertations, which qualitatively examined the parenthood experiences of refugees, asylum-seekers and undocumented migrants. We summarized study characteristics and performed a thematic analysis across the studies. Results One hundred thirty eight studies met inclusion criteria. All but three were conducted in high-income countries, mainly in the US. Migrants studied were mostly undocumented from Latin America and refugees from Sub-Saharan Africa. Almost all studies (93%) included mothers; about half (47%) included fathers; very few (5%) included extended family members. We identified three integrative themes: 1) experiencing hardship and/or loss in the context of precarious migration and past traumas; 2) building resilience and strength by bridging language, norms and expectations; and 3) living transnationally: obligations, challenges and resources. Each theme contributed to shaping the parenthood experience; the transnationalism theme intersected with the themes on hardship and loss and resilience and strength. Conclusion More research is needed with fathers, extended family members, asylum-seekers and in the LMIC context. A transnational lens needs to be applied to programs, policies and future research for refugee, asylum-seeker and undocumented migrant parents. Addressing transnational concerns (family separation and reunification), acknowledging transnational resources, fostering a transnational family identity and conducting transnational and longitudinal studies are potentially pivotal approaches for this sub-population of parents.